Simulation of Arctic Diamond Dust, Ice Fog, and Thin Stratus Using an Explicit Aerosol–Cloud–Radiation Model - Girard, Eric; Blanchet, Jean-Pierre (2001)
In support to the development of the Northern Aerosol Regional Climate Model, a single column model with explicit aerosol and cloud microphysics is described. It is designed specifically to investigate cloud–aerosol interactions in the Arctic. A total of 38 size bins discretize the aerosol and cloud spectra from 0.01- to 500-μm diameter. The model is based on three equations describing the time evolution of the aerosol, cloud droplet, and ice crystal spectra. The following physical processes are simulated: coagulation, sedimentation, nucleation, coalescence, aggregation, condensation, and deposition. Further, the model accounts for the water–ice phase interaction through the homogeneous and heterogeneous freezing, ice nuclei, and the Bergeron effect. The model has been validated against observations and other models. In this paper, the model is used to simulate diamond dust and ice fog in the Arctic during winter. It is shown that simulated cloud features such as cloud phase, cloud particle diameter, number concentration, and mass concentration are in agreement with observations. The observed vertical structure of mixed-phase cloud is also reproduced with the maximum mass of liquid phase in the upper part of the cloud. Based on simulations, a hypothesis is formulated to explain the thermodynamical unstable mixed-phase state that can last several days in diamond dust events. The ice supersaturation time evolution is assessed and is compared to its evolution in cirrus clouds. It is shown that the supersaturation relaxation time, defined as the time required for supersaturation to decrease by a factor e, is more than 10 times the value found in cirrus clouds. Finally, the radiative contribution of arctic diamond dust and ice fog to the downward longwave radiation flux at the surface is evaluated and compared to observations.